KETENTUAN YANG MENGATUR TENTANG TINDAK PIDANA PELANGGARAN PENYIMPANGAN SEKSUAL YANG DILAKUKAN OLEH OKNUM MILITER - Azis, Nur Azmi; Simangunsong , Frans (Universitas Wiralodra, 2024)
In this research, the author's aim is to provide a comprehensive understanding regarding the legal handling of cases of sexual deviation involving military personnel. The author in this research uses normative research methods, with a focus on presenting legal principles, legal rules and legal doctrine that are relevant to answering the legal issues faced. The author in this study will discuss sexual deviation in the context of the military environment. The problem that is the focus of this research is